The Impact of Bilateral Range of Motion Exercises on Upper Limb Muscle Strength in Stroke Patients - Marlin Brigita; Niken Nita Yogi Febriana; Robby Rahmadi Akbar (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2024)
Stroke is a condition that arises due to a disruption in blood circulation in the brain, which results in the death of brain tissue, causing a person to suffer paralysis and even death. Exercise activities are part of a rehabilitation program that enhances patient movement. Exercise therapy, such as range of motion (ROM) exercises, is the movement of a joint through its entire range in all appropriate directions. This research method is quantitative, with a one-group pre-test and post-test design. A sample of 24 respondents was taken using the purposive sampling technique at RSUP Dr. Sitanala Tangerang. Data collection used two instruments, namely a bilateral ROM checklist and a guide to muscle strength values. Data analysis used the paired t-test in univariate analysis and bivariate analysis. The results of statistical tests using the t-dependent test (paired sample t-test) showed that of the 24 respondents, the mean pre-test value was ± 3.38 and the mean post-test was ± 4.50. The statistical test results show a p-value of 0.000 (α<0.05). Therefore, we can conclude that ROM has an influence on increasing muscle strength in stroke patients.